#1**+3 **

Note that (w-13) (w-13) = (w-13)^2

So we have (w-13)^2 = 16

Taking the square root of both sides, we have

(w-13) = 4

Add 13 to both sides .......so, w = 17

So we have (w-13)^2 = 16

Taking the square root of both sides, we have

(w-13) = 4

Add 13 to both sides .......so, w = 17

CPhill Mar 19, 2014

#2**0 **

Remeber that: (a-b) ^{2} = a ^{2}-2ab+b ^{2}

So you have:

(w-13)(w-13)=16 =>

(w-13)^{2}=16 =>

w^{2}-2w*13+13 ^{2}=16 =>

w^{2}-26w+153=0 =>

Check, Quadratic equation:*http://en.wikipedia.org/wiki/Quadratic_equation*

So you have:

(w-13)(w-13)=16 =>

(w-13)

w

w

Check, Quadratic equation:

w=(26+sqrt(26^2-4*153))/2

__OR__

w=(26-sqrt(26^2-4*153))/2

So there are__2 solutions!__

**w=9 ** __OR__ **w=17**

Dms

So there are

Dms

Dms Mar 19, 2014

#3**0 **

FIRST:

Equal your equation to ZERO and do the equation of the (), w^{2} - 26w + 169 = 16 /////// w ^{2} - 26w + 153 = 0

SECOND:

Use the formula

(-b +/- sqrt(b^{2} - 4ac))/2a

You'll have w_{1} and w _{2}

femmy:(w-13)(w-13)=16

FIRST:

Equal your equation to ZERO and do the equation of the (), w

SECOND:

Use the formula

(-b +/- sqrt(b

You'll have w

solve((w-13)(w-13)=16, w)

samgelinas Mar 19, 2014